Gene transfer of Alcaligenes eutrophus JMP134 plasmid pJP4 to indigenous soil recipients. - DiGiovanni, G D (1996)
This study evaluated the potential for gene transfer of a large catabolic plasmid from an introduced organism to indigenous soil recipients. The donor organism Alcaligenes eutrophus JMP134 contained the 80-kb plasmid pJP4, which contains genes that code for mercury resistance. Genes on this plasmid plus chromosomal genes also allow degradation of 2,4-dichloruphenoxyacetic acid (2,4-D). When JMP134 was inoculated into a nonsterile soil microcosm amended with 1,000 micrograms of 2,4-D g-1, significant (10(6) g of soil-1) populations of indigenous recipients or transconjugants arose. These transconjugants all contained an 80-kb plasmid similar in size to pJP4, and all degraded 2,4-D. In addition, all transconjugants were resistant to mercury and contained the tfdB gene of pJP4 as detected by PCR. No mercury-resistant, 2,4-D-degrading organisms with large plasmids or the tfdB gene were found in the 2,4-D-amended but uninoculated control microcosm. These data clearly show that the plasmid pJP4 was transferred to indigenous soil recipients. Even more striking is the fact that not only did the indigenous transconjugant population survive and proliferate but also enhanced rates of 2,4-D degradation occurred relative to microcosms in which no such gene transfer occurred. Overall, these data indicate that gene transfer from introduced organisms is an effective means of bioaugmentation and that survival of the introduced organism is not a prerequisite for biodegradation that utilizes introduced biodegradative genes.